ANALISIS KESEHATAN DAN KESELAMATAN KERJA PADA PRODUKSI PABRIK TAHU PAK RAHMAN DENGAN MENGGUNAKAN METODE HAZARD IDENTIFICATION AND RISK ASSESMENT (HIRA) - Gatam Mandala Krida; Andung Jati Nugroho (JURNAL ILMIAH NUSANTARA, 2024)
In the business world, especially in the food industry sector, competition has always centered on improving time efficiency, proper use of equipment, productive labor, and capacity to produce goods. Labor affects production productivity significantly, therefore, the implementation of appropriate OHS standards in all stages of production is essential to ensure the comfort and safety of workers, so that they can achieve optimal production results. Pak Rahman's Tofu Factory is an UMKM making tofu Work accidents that often occur are, exposed to sparks during the frying process, injured during the cutting process, blistered skin during the boiling process, skin irritation during the washing process. The purpose of this study is to analyze the potential hazards at Pak Rahman's Tofu Factory and submit recommendations for risk control. To identify and evaluate risks by considering the likelihood and severity of events, the HIRA method is needed to complete this research. The results of risk evaluation using the hazard identification and risk assessment method show that there are no risks with a high risk category, risks that have a moderate risk category have a value of 82%, while risks with a low risk category have a value of 18%.